2017
DOI: 10.1007/s10151-017-1664-2
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the treatment of anal fissure

Abstract: LIS is superior to non-surgical therapies in achieving sustained cure of fissure. Calcium channel blockers were more effective than GTN and with less risk of headache, but with only a low quality of evidence. Anal incontinence, once thought to be a frequent risk with LIS, was found in various subgroups in this review to have a risk between 3.4 and 4.4%. Among the surgical studies, manual anal stretch performed worse than LIS in the treatment of chronic anal fissure in adults. For those patients requiring surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 147 publications
4
76
1
2
Order By: Relevance
“…Treatment is aimed at reducing spasm of the IAS, relieving pain and promoting healing of the ulcer. The most effective method for CAF healing is lateral sphincterotomy [2]. Although this procedure is associated with healing rates of greater than 90% [3, 4], there is permanent weakening of the IAS and this may lead to incontinence of gas (6–9%), liquid (6–8%) and solid stool (1%) [5, 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment is aimed at reducing spasm of the IAS, relieving pain and promoting healing of the ulcer. The most effective method for CAF healing is lateral sphincterotomy [2]. Although this procedure is associated with healing rates of greater than 90% [3, 4], there is permanent weakening of the IAS and this may lead to incontinence of gas (6–9%), liquid (6–8%) and solid stool (1%) [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Although non-permanent, this causes a lowering of resting pressure for a temporary period allowing healing of the fissure. Success rates (65–75%) are significantly lower than those associated with surgical sphincterotomy [2, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Medical management has a much-reduced incidence of the dreaded complication of faecal incontinence but has a higher recurrence rate (around 50% for medical management as compared to 3-6% for LIS) [23][24][25]. This recurrence rate is similar for both calcium channel blockers and nitrates.…”
Section: Pharmacological Managementmentioning
confidence: 99%
“…The change in practice was extensively studied and represented in recent reviews and meta-analyses. It has been confirmed that manual anal stretch had higher rate of incontinence and was not more effective than internal sphincterotomy [6][7][8].…”
Section: Introductionmentioning
confidence: 98%